Evaluating motivation of construction workers: a comparison of fuzzy rule-based model with the traditional expectancy theory - Yeheyis, Muluken; Reza, Bahareh; Hewage, Kasun; Y. Ruwanpura, Janaka; Sadiq, Rehan (Journal of Civil Engineering and Management, 2016)
Measuring workers’ performance and the level of motivation is of paramount importance as the productivity of workers at a workplace primarily depends upon their level of motivation. However, measuring the level of workers’ motivation at workplace is not always straightforward because the workers’ motivation is a function of various personal and external factors. This paper proposes a fuzzy rule-based model for evaluating the motivation level of construction workers using their working patterns. The motivation level evaluated using the fuzzy rule-based model was compared with motivational levels determined by the traditional Vroom’s expectancy theory or Expectancy-Instrumentality-Valence (EIV) method. EIV method used questionnaire surveys and interviews to determine workers’ motivation. The results of fuzzy rule-based models aligned closely with the EIV model, especially for the middle range of motivation levels. Compared to traditional EIV model, the fuzzy rule-based system is simple to implement and found to be very pragmatic in construction field settings.